(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Regional anaesthesia in children provides the advantage of reduced requirements of other anaesthetic agents and of excellent analgesia introduction. Rational use of adjuvant with local anaesthetic in caudal route for prolonged optimal analgesia in paediatric population. Objectives To evaluate the quality and duration of postoperative analgesia in children undergoing subumbilical surgeries with caudally administered mixture of tramadol and bupivacaine. Methods Sixty children of ASA physical status I & II scheduled for elective subumbilical surgery were included in this prospective case-control study. Children were randomly assigned to receive caudal analgesia with plain bupivacaine (Group-I) and a mixture of tramadol-bupivacaine (Group-II) respectively. Blood pressure, heart rate, oxygen saturation and duration of analgesia were recorded postoperatively. Results Study revealed that mean duration of caudal analgesia in Group-I and Group-II were 245.67 ± 6.94 and 612.05 ± 16.49 minutes respectively which was significantly longer (P<0.001) in Group-II. Mean number of postoperative analgesics were 2.97±0.50 and 1.78±0.50 in Group-I and Group-II which was statistically highly significant (P=0.000). Postoperative nausea and vomiting was significantly high in Group-II (P=0.019). Conclusion Combination of tramadol with bupivacaine results in prolonged analgesia when administered in caudal route. In addition, tramadol is more useful in young children considering less respiratory depression than other opioids. DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18172 Journal of BSA, 2009; 23(2): 42-46